Cortico‐striatal functional connectivity and cerebral small vessel disease: Contribution to mild Parkinsonian signs. Issue 2 (27th December 2021) - Hengenius, James B.; Bohnen, Nicolaas I.; Rosso, Andrea; Huppert, Theodore J.; Rosano, Caterina
ABSTRACT: Background and Purpose: Mild Parkinsonian signs (MPS) are common in older adults. We hypothesized that MPS are associated with lower functional connectivity (FC) in dopamine‐dependent cortico‐striatal networks, and these associations vary with white matter hyperintensity (WMH), a risk factor for MPS. Methods: We examined resting‐state functional MRI in 266 participants (mean age 83; 57% female; 41% African American) with data on MPS (Unified Parkinson's Disease Rating Scale), demographics, cognition, muscle‐skeletal, and cardiometabolic health. FC between cortex and striatum was examined separately for sensorimotor, executive, and limbic functional subregions. Logistic regression tested the association of FC in each network with MPS, adjusted for covariates. Interactions of FC by WMH were tested; and analyses were repeated stratified by WMH above/below the median. Results: Compared to those without MPS, those with MPS had lower cortico‐striatal FC in the left executive network (adjusted odds ratio [95% confidence interval], p ‐value: 0.188 [0.043, 0.824], .027). The interaction with WMH was p = .064; left executive FC was inversely associated with MPS for high WMH (0.077 [0.010, 0.599], .014) but not low WMH participants (1.245 [0.128, 12.132], .850). Conclusions: MPS appear related to lower executive network FC, robust to adjustment for other risk factors, and stronger for those with higher burden of WMH. Future longitudinal studies should examine the interplay between cerebral small vessel disease and connectivity influencing MPS.